2016
DOI: 10.1212/wnl.0000000000002337
|View full text |Cite
|
Sign up to set email alerts
|

Practice guideline update summary: Corticosteroid treatment of Duchenne muscular dystrophy

Abstract: Methods: We systematically reviewed the literature from January 2004 to July 2014 using the AAN classification scheme for therapeutic articles and predicated recommendations on the strength of the evidence.Results: Thirty-four studies met inclusion criteria.Recommendations: In children with DMD, prednisone should be offered for improving strength (Level B) and pulmonary function (Level B). Prednisone may be offered for improving timed motor function (Level C), reducing the need for scoliosis surgery (Level C),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
134
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 212 publications
(141 citation statements)
references
References 40 publications
1
134
0
6
Order By: Relevance
“…The first studies focusing on glucocorticoid therapy for DMD boys have demonstrated that prednisone, in a dose of 0.75/mg/Kg/daily, can achieve substantial effects on motor function in a six-month period 4,6,43 . Later studies have demonstrated that different drugs with an equivalent dose show similar effects: prednisone or prednisolone 0.75mg/Kg daily (Level of evidence: 1A, Class of Recommendation: A) 35 or deflazacort 0.9 to 1mg/Kg daily (Level of evidence: 3C, Class of Recommendation: C) 44,45 .…”
Section: Which Glucocorticoid Should Be Prescribed and What Dose Is Rmentioning
confidence: 99%
See 3 more Smart Citations
“…The first studies focusing on glucocorticoid therapy for DMD boys have demonstrated that prednisone, in a dose of 0.75/mg/Kg/daily, can achieve substantial effects on motor function in a six-month period 4,6,43 . Later studies have demonstrated that different drugs with an equivalent dose show similar effects: prednisone or prednisolone 0.75mg/Kg daily (Level of evidence: 1A, Class of Recommendation: A) 35 or deflazacort 0.9 to 1mg/Kg daily (Level of evidence: 3C, Class of Recommendation: C) 44,45 .…”
Section: Which Glucocorticoid Should Be Prescribed and What Dose Is Rmentioning
confidence: 99%
“…Since DMD patients have, in general, a lifelong prospect of glucocorticoid usage, an optimal follow-up schedule is necessary for monitoring possible side effects 6 . An ideal outline of routine consultations takes into account three relevant factors: the patient' s age, the type of glucocorticoid prescribed and the drug regimen adopted.…”
Section: Which Glucocorticoid Should Be Prescribed and What Dose Is Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas corticosteroids and supportive measures have improved overall prognosis and lifespan, cardiomyopathy continues to be relentlessly progressive and has become a major cause of death 8. Recent guidelines emphasize the need for early diagnosis and aggressive treatment for cardiomyopathy in DMD 9.…”
Section: Introductionmentioning
confidence: 99%